Review of Magnetoelectric Effects on Coaxial Fibers of Ferrites and Ferroelectrics - Sujoy Saha; Sabita Acharya; Ying Liu; Peng Zhou; Michael R. Page; Gopalan Srinivasan (Applied Sciences)
Composites of ferromagnetic and ferroelectric phases are of interest for studies on mechanical strain-mediated coupling between the two phases and for a variety of applications in sensors, energy harvesting, and high-frequency devices. Nanocomposites are of particular importance since their surface area-to-volume ratio, a key factor that determines the strength of magneto-electric (ME) coupling, is much higher than for bulk or thin-film composites. Core–shell nano- and microcomposites of the ferroic phases are the preferred structures, since they are free of any clamping due to substrates that are present in nanobilayers or nanopillars on a substrate. This review concerns recent efforts on ME coupling in coaxial fibers of spinel or hexagonal ferrites for the magnetic phase and PZT or barium titanate for the ferroelectric phase. Several recent studies on the synthesis and ME measurements of fibers with nickel ferrite, nickel zinc ferrite, or cobalt ferrite for the spinel ferrite and M-, Y-, and W-types for the hexagonal ferrites were considered. Fibers synthesized by electrospinning were found to be free of impurity phases and had uniform core and shell structures. Piezo force microscopy (PFM) and scanning microwave microscopy (SMM) measurements of strengths of direct and converse ME effects on individual fibers showed evidence for strong coupling. Results of low-frequency ME voltage coefficient and magneto-dielectric effects on 2D and 3D films of the fibers assembled in a magnetic field, however, were indicative of ME couplings that were weaker than in bulk or thick-film composites. A strong ME interaction was only evident from data on magnetic field-induced variations in the remnant ferroelectric polarization in the discs of the fibers. Follow-up efforts aimed at further enhancement in the strengths of ME coupling in core–shell composites are also discussed in this review.